A construção de uma política nacional de arquivos: bases conceituais, ações e problemas - Ana Marcia Lutterbach Rodrigues (2013)
This paper aimed investigates issues relevant to a national archival policy. Starting from its context in the Information Society and considering the limitations imposed by the absence of a national information policy, the concepts that that goal involves are defined and the current situation of public archival information in Brazil is outlined. This delimitation focuses on identifying problems and intervening factors in structures and processes of control and access to organic documentary information both from of public and private interest, whereas a policy is proposed mainly to solve problems. The research methodology focused on the literature review and institutional publications geared to public documents in order to draw the political and economic context in which the information processes are currently developed nowadays. It also includes extended to sources at entities of the legislative, executive and judicial, state and municipal institutions, located in the city of Belo Horizonte / MG, in order to create an empirical reference of for archival practices. The problems identified, particularly in the literature, are then related to the conditions in which the practices for public documents are developed, to endorse them. Finally, these problem-conditions are translated as a "political action", since they define the current status of archives, and some basic procedures of that would lay groundwork for the construction of a national archives policy are enumerated, in order to make available the public organic documents in the service of society.